Thromboprophylactic low-molecular-weight heparin versus standard of care in unvaccinated, at-risk outpatients with COVID-19 (ETHIC): an open-label, multicentre, randomised, controlled, phase 3b trial - Cools, F; Virdone, S; Sawhney, J; Lopes, RD; Jacobson, B; Arcelus, JI; Hobbs, FDR; Gibbs, H; Himmelreich, JCL; MacCallum, P; Schellong, S; Haas, S; et al. (Elsevier, 2022)
Background: COVID-19 is associated with inflammation and an increased risk of thromboembolic complications. Prophylactic doses of low-molecular-weight heparin have been used in hospitalised and non-critically ill patients with COVID-19. We aimed to evaluate the efficacy and safety of prophylactic low-molecular-weight heparin (enoxaparin) versus standard of care (no enoxaparin) in at-risk outpatients with COVID-19.